Exploring distance in security force assistance: The case of NATO Mission Iraq - Maria-Louise Clausen; Peter Albrecht (Danish Institute for International Studies (DIIS), 2022)
The West's diminished belief in its own transformative capabilities has led to a preference for stabilisation over statebuilding interventions. This working paper explores how this has led to an increased Western focus on applying distance between the intervening state and the subject of intervention, focusing specifically on the North Atlantic Treaty Organisation (NATO), as the foremost Western security organisation. The working paper argues that current security force assistance applies a dual strategy that combines local partner support - the advising, training, and equipping of local partners to plan and execute ground operations - with targeted strikes and surveillance using drones. This distance, we suggest, actually lessens the effectiveness of SFA, as these relationships suffer from many of the weaknesses associated with patron-client relations as described in the proxy war literature. In the second part of the paper, we trace how SFA is done by the NATO Mission Iraq (NMI). This is an important test case for demonstrating the influential idea that the security of NATO member states can be ensured by stabilising the alliance's periphery
Keywords: 330; security sector reform; global South; NATO in Iraq; SFA